Expert knowledge, evidence, and information - Piazza, Tommaso (Veritas (Porto Alegre), 2010)
In this paper I argue that the existence of expert knowledge potentially poses a problem for Evidentialism, the view that a person’s justification supervenes on the evidence this person has. An expert is the kind of person from which knowledge (or justified belief) is expected in situations in which a non-expert would normally not attain knowledge (or justified belief); so, potentially, the epistemic status of their beliefs differ even if the evidence they possess seems to be the same. A viable solution to this problem has to show that, appearances to the contrary, the expert and the non-expert, in the problematic cases, do not possess the same evidence. I propose a solution to this problem by defending a principle that specifies the conditions under which a piece of information should be counted as evidence.